Love Influences Reproductive Success in Humans - Sorokowski, Piotr; Sorokowska, Agnieszka; Butovskaya, Marina; Karwowski, Maciej; Groyecka, Agata; Wojciszke, Bogdan; Pawłowski, Bogusław (Frontiers in Psychology, 2017)
As love seems to be universal, researchers have attempted to find its biological basis. However, no studies to date have shown its direct association with reproductive success, which is broadly known to be a good measure of fitness. Here, we show links between love, as defined by the Sternberg Triangular Theory of Love, and reproductive success among the Hadza – traditional hunter-gatherer population. We found that commitment and reproductive success were positively and consistently related in both sexes, with number of children showing negative and positive associations with intimacy and passion, respectively, only among women. Our study may shed new light on the meaning of love in humans’ evolutionary past, especially in traditional hunter-gatherer societies in which individuals, not their parents, were responsible for partner choice. We suggest that passion and commitment may be key factors that increase fitness, and therefore that selection promoted love in human evolution. However, further studies in this area are recommended.